Direct blood analysis of Bartonella bacilliformis Multi Locus Sequence Typing in patients with Oroya’s fever during a Peruvian outbreak - Pons, Maria J., Silva, Wilmer, Gomes, Cláudia, Ruiz, Joaquim, Del Valle Mendoza, Juana Mercedes (2015)
The bacteria Bartonella bacilliformis is the etiological agent of Carrion’s disease, which is a neglected poverty-related disease, affecting Mountain Andean valleys of Peru, Colombia and Ecuador. This disease, in absence of treatment presents a high mortality during the acute phase, called Oroya’s Fever. The second phase is characterized by the development of dermal eruptions, known as “Peruvian wart”. This bacterium is a fastidious slow growing microorganism, being difficult and cumbersome to culture and isolate from clinical sources. Then, the available data about phylogenetic relationship in clinical samples are really scarce, but suggesting high variability. The aim of the study was to perform direct blood analysis of B. bacilliformis Multi Locus Sequence Typing (MLST), a genotyping tool, in patients with Oroya fever during an outbreak. The present study demonstrate that the direct blood MLST PCR is a technique useful in the phylogenic characterization of this fastidious microorganism endemic from Andean regions. In this study, we demonstrate that the outbreak of Oroya’s fever was caused by closely related Sequence Typing (ST) microorganisms and, additionally, new STs have been described.